ANTIOXIDANT METABOLISM IN WATER STRESSED PEANUT TREATED WITH DINICONAZOLE - RIVERO, G C (SEAMEO BIOTROP, 1992)
The response of alpha-tocopherol, glutathione and ascorbate was studied in peanut (Arachis hypogea L., cv. NC-17) subjected to water stress and treated with a triazole fungicide, diniconazole (DINI). There was no significant difference in alpha-tocopherol levels between control and DINI treated plants. However, a 14% increase was observed in alpha-tocopherol level in DINI treated, water stressed plants compared to water stressed plants. Total glutathione in DINI treated stressed plants increased by 13 and 31% over control and water stressed plants, respectively. Ascorbate levels decreased significantly in all treatments compared to the control. These results indicate that DINI alleviates the oxidative damage caused by water stress by increasing total glutathione levels. However, DINI does not seem to affect alpha-tocopherol and ascorbate levels in peanuts under water stress.